Kontribusi Pemikiran Tokoh Pendidikan Islam terhadap Transformasi Pendidikan Islam Berbasis Karakter dan Keilmuan - M. Nur Saefullah; Ahmad Saad Nurifai; Khidir Mansyur; Mulyanto Abdullah Khoir (TSAQOFAH, 2026)
The transformation of Islamic education in the global era faces challenges in integrating character formation, the strengthening of knowledge, and responses to the development of contemporary science, particularly because there remains a tendency toward a dichotomy between spiritual, moral, and academic dimensions in educational practice. This study aims to analyze the contribution of Islamic educational thinkers’ ideas to the transformation of Islamic education based on character and knowledge and to explain their relevance to the development of the contemporary Islamic education system. This study employed a qualitative approach using the library research method. Data were obtained from books, reputable scholarly articles, classical works, and academic documents discussing the thought of Islamic educational figures. The data were analyzed using content analysis techniques through the stages of data reduction, categorization, interpretation, and conceptual synthesis. The findings show that the thought of Islamic educational figures contributes significantly to developing an educational paradigm that balances the strengthening of faith, morality, intellectuality, and mastery of knowledge. The main values identified include the integration of knowledge and religion, character formation, educator exemplarity, the development of adab, student-centered learning, and the strengthening of scientific culture. These findings affirm that the transformation of Islamic education based on character and knowledge should be directed toward curriculum reconstruction, the strengthening of educator competence, and the integration of Islamic values with developments in science and technology. The implications of this study provide a conceptual framework for the development of educational policy, curriculum innovation, and learning practices in Islamic educational institutions to strengthen the quality of graduates who possess character, integrity, and competitiveness in the 21st century.